1987
DOI: 10.1080/10862968709547610
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Directing Study in Combined Reading and Writing Activity

Abstract: An experiment investigated the memorial effects of three different writing tasks and worksheet exercises assigned as study activities to accompany reading. High school boys and girls read and recalled a pretreatment target text and then read a sequence of topically related passages and reacted to each by paraphrasing, formulating questions, comparing and contrasting, or completing matching exercises on worksheets. Afterward, the students again recalled the target text. A comparison of information given in rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…He suggested that the permanence of the written word, the explicitness required for effective written communication, the richness of discursive tools for refining ideas, and the active nature of writing all converge to make writing an extremely powerful process for shaping thought. Hayes (1987) utilized the organizing-demands hypothesis to explain how this might work: "Writing may achieve its effects by the demands it places on learners to organize language" (p. 334). Britton et al (1975) reported that British students do more writing in content areas than in the English classroom.…”
Section: Concerns About Writing and Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…He suggested that the permanence of the written word, the explicitness required for effective written communication, the richness of discursive tools for refining ideas, and the active nature of writing all converge to make writing an extremely powerful process for shaping thought. Hayes (1987) utilized the organizing-demands hypothesis to explain how this might work: "Writing may achieve its effects by the demands it places on learners to organize language" (p. 334). Britton et al (1975) reported that British students do more writing in content areas than in the English classroom.…”
Section: Concerns About Writing and Learningmentioning
confidence: 99%
“…Newell concluded that analytic essay writing encouraged the learners to integrate new information with relevant prior topical knowledge. Hayes (1987) investigated the effect of combining different writing tasks with reading on the hierarchical organization of information recalled later. This recall measure allowed Hayes to compare the proportion of top-level and low-level information included by students.…”
Section: Writing Learning and Thinking Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies suggest that writing can help students learn even without such training. More specifically, students asked to compare and contrast ideas, explain concepts, support a viewpoint, or share their thoughts with others showed greater learning gains than students who did not perform these assignments (Audet et al 1996;Fellows 1994;Hand et al 2002;Hayes 1987;Voss and Wiley 1997). One characteristic common to many of these studies was that the writing assignments asked students to use an argument format.…”
Section: Metacognition and Writing-to-learnmentioning
confidence: 93%
“…The forward search hypotheses were attributed to Bruner (1966), Emig (1977), and Donald (1991) because these theorists asserted that writers transform their ideas by ongoing analyses of their texts in terms of expanding inferences, reviewing idea development, noting contradictions, and making appropriate revisions. Bereiter and Scardamalia (1987), Halliday and Martin (1993), and Hayes (1987) were among several of those identified as contributing to the genre-related hypotheses, which maintains that the use of different generic frameworks and knowledge of the micro and macro structure of texts enables students to identify the relationships between ideas and clarify understanding of content. The backward search hypotheses, which Klein attributed to Flower and Hayes (1980;, Vygotsky (1962), and Bruner (1966), among others, argue that students learn through writing by setting and addressing rhetorical and content goals.…”
Section: Introductionmentioning
confidence: 99%